2019
DOI: 10.21202/1993-047x.13.2019.3.1412-1429
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Injustice and Police Misconduct: Predicting Organizational Defiance Among Police Officers

Abstract: Цель: изучение влияния организационной несправедливости на нарушение дисциплины сотрудниками правоохранительных органов в Соединенных Штатах Америки. Методы: диалектический подход к познанию социальных явлений, позволяющий проанализировать их в историческом развитии и функционировании в контексте совокупности объективных и субъективных факторов, который определил выбор следующих методов исследования: формально-логический, сравнительно-правовой, социологический. Результаты: многочисленные исследования подтвержд… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Thus, organizational justice has evolved from a three-to a four-dimensional framework, although interactional justice is the least studied among the initial core dimensions. While the framework's effectiveness in understanding police misconduct has generally been accepted, especially among scholars of distributive and procedural justice (e.g., Reynolds & Helfers, 2019;Wolfe & Piquero, 2011), this paper extends the narrative primarily on distributive justice due to its focus on outcomes. Adams (1963) and Leventhal (1976) are credited with shaping what is described as distributive justice.…”
Section: Theory Of Organizational Justicementioning
confidence: 97%
“…Thus, organizational justice has evolved from a three-to a four-dimensional framework, although interactional justice is the least studied among the initial core dimensions. While the framework's effectiveness in understanding police misconduct has generally been accepted, especially among scholars of distributive and procedural justice (e.g., Reynolds & Helfers, 2019;Wolfe & Piquero, 2011), this paper extends the narrative primarily on distributive justice due to its focus on outcomes. Adams (1963) and Leventhal (1976) are credited with shaping what is described as distributive justice.…”
Section: Theory Of Organizational Justicementioning
confidence: 97%
“…This area of research related to police use of force and police use of procedural justice has addressed officer satisfaction with their jobs and duties as law enforcement officers. This is relevant to how police officers perform their duties during police-citizen encounters (PEW Research Center, 2017;Van Craen, 2016;Van Craen & Skogan, 2017;Reynolds & Helfers, 2019;Sun et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bandura (1977), Van Craen (2016), and Chapelle and Piquero (2004 suggested that social learning theory explains how individuals learn through socialization with those that influence them the most. In the case of law enforcement officers, peers and supervisors influence officers in learning to behave in performing their operationalized duties (Reynolds & Helfers, 2019). Law enforcement superiors set the standard for practicing procedural justice in the training, encouraging the practice of procedural justice in the field.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, employees, conceive fairness from the organizational work environment and respond based on such judgements. This suggests that behavioural patterns are shaped by the perception of fairness in the workplace and not by the individual's personality and characteristics (Reynolds and Helfers 2019). The police, like other organizations, are not immune from these work-related behaviours by employees.…”
Section: Organizational Theory Of Police Behaviourmentioning
confidence: 99%